Brain abscess due to clostridium celerecrescens: first report and literature review - Ganzhi Liu; Tiange Chen; Xiaobo Tian; Ying Ai; Ziyang Chen; Jinfang Liu; Zhongyi Sun (BMC Infectious Diseases)
Abstract Background Brain abscess caused by atypical pathogens presents significant diagnostic and therapeutic challenges. The unusual clinical presentations, coupled with incomplete or inaccurate patient histories, often result in misdiagnosis and inappropriate treatment. Case presentation We report a case of a retained intracranial bamboo foreign body resulting in a brain abscess. A female adolescent presented with a newly developed mass on the eyelid. Medical imaging identified a foreign body that had penetrated the frontal lobes via the transorbital route, leading to the formation of a brain abscess. The foreign body was successfully removed through transnasal endoscopy. Inflamed tissue adherent to the foreign body was cultured and analyzed using metagenomic next-generation sequencing (mNGS), which identified Clostridium celerecrescens as the causative pathogen. The patient fully recovered after surgical debridement and two weeks of antibiotic therapy. Conclusions Infections caused by C. celerecrescens are exceedingly rare in clinical practice. This case highlights the bacterium’s ability to adhere to a bamboo foreign body, leading to the formation of a rare brain abscess. mNGS proves to be a valuable diagnostic tool for identifying uncommon infectious agents.